Bailing Out Sovereign Debt : An Old Texan Precedent - Richard C. K. Burdekin (Claremont McKenna College, Department of Economics, 2004)
The fate of the distressed debt issued by the 1836-1845 Republic of Texas has received surprisingly little attention. Annexation by the United States was almost certainly a necessary condition for the debt rising from the pennies-on-the-dollar values seen in the early 1840s. But the largest gains awaited legislation in the early 1850s that fixed the repayment terms on the debt. Statistical analysis confirms the link between the debt price and actual, or anticipated, congressional actions on the debt settlement after 1844.
Keywords: 330; Öffentliche Schulden; Umschuldung; Staatsbankrott; Finanzgeschichte; Schatzpapier; Texas; Vereinigte Staaten